2014
DOI: 10.1111/ans.12531
|View full text |Cite
|
Sign up to set email alerts
|

Institutional review of patients presenting with suspected appendicitis

Abstract: Elevated WCC, NC and CRP were all associated with acute appendicitis and SA in adults only. CT is useful for refining the diagnosis in adult females. A combination of inflammatory markers, ultrasound and AlvS may be used selectively to complement or maximize the advantages of CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…A recent publication had a 27 % negative appendectomy rate and the authors justify their low threshold to operate by stating that it avoids perforation [ 73 ]. Others disagree and found that delaying surgical intervention did not put the patient at risk and may have actually improved patient outcomes [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent publication had a 27 % negative appendectomy rate and the authors justify their low threshold to operate by stating that it avoids perforation [ 73 ]. Others disagree and found that delaying surgical intervention did not put the patient at risk and may have actually improved patient outcomes [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous decades, a NAR between 15% and 25% has been accepted as reasonable . The published literature estimating the NAR in Australia is predominantly based upon single‐centre retrospective audits …”
Section: Discussionmentioning
confidence: 99%
“…Research in this area in Australia has predominantly been limited to single‐centre retrospective audits of individual institutions . Although single‐centre audits are important for quality improvement purposes for individual organizations, they can be difficult to apply in a broader sense and inform systemic policy and procedure guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of disease in children aged birth to 4 years is about 1 to 2 cases per 10,000 children per year, reaching 25 cases per 10,000 children per year in older children [4]. The prevalence of disease in boys is twice that of girls with a brief distinction in different countries [5], [6]. The prevalence of acute appendicitis in developed countries is higher probably due to low fibre diet, genetic susceptibilities, as well as different patterns in gastrointestinal flora [7].…”
Section: Introductionmentioning
confidence: 99%